MCDM APPLICATION FOR BACTERIA MEASUREMENT DEVICES - Shaalan, Maryam Khalid; Abdulkhalik, Humam Abduljabbar; Amran, Naba Ndhm (PT. Antis International Publisher, 2024)
This study explores the innovative use of gas sensors to detect bacterial infections. The fundamental reliance of this technique is on monitoring fluctuations in the quantities of biogenic gases produced by bacteria during their growth. Through analysis, these sensors can accurately identify the kind and severity of a disease by detecting chemicals such as ammonia and hydrogen sulphide. Preliminary studies indicate that gas sensors provide a rapid and non-intrusive method for diagnosing bacterial infections. Additionally, they possess a notable level of sensitivity and precision. This technology improves clinical results and reduces the transmission of infections, enabling healthcare personnel to administer the appropriate medications promptly